Prolidase deficiency. Report of four cases. - Amato, S.; Milioto, M.; Papadia, F.; Caprio, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 1997)
Four cases of prolidase deficiency were reported. The first case, a 25-year-old female patient, was particularly complex. She presented chronic ulcers of the lower limbs, diffuse telangiectasias of the forearms and hands, mental retardation, bone and dental abnormalities, poliosis, hirsutism and splenomegaly. The pathogenesis and the disappointing treatment of this inherited disorder are discussed.